A Patient With a Chronic Cough: An Unexpected Case of Calcium Pill Aspiration. (February 2019) - Poudel, Pooja; Chu, Andrew; Mirchia, Kanish; Paul, Manju
Foreign body aspiration is a life-threatening medical condition that requires prompt action. Delayed diagnosis is associated with long-term serious complication often leading to death. In adults, it can remain undetected for a long period of time. The patient gives a long history of a cough, which clinicians often ignore. A chest radiograph is unreliable to exclude the disease as it may not show radiolucent objects. Diagnostic bronchoscopy is necessary to exclude the disease. We report a case of 70-year-old woman who had a 1-month history of a cough and was admitted for shortness of breath, and on further evaluation, we incidentally detected calcium tablets in her bronchus. The present case demonstrates the need for early bronchoscopy especially when the cause of a chronic cough is not known.